398 Outcome of Laparoscopic Cholecystectomy in Patients Over 80 Years Old. (12th October 2021) - Gumaa, D; Hunt, A; Karunaratne, D; Shresta, S; Al-Robaie, B
Abstract: Background: Gallstone disease is a common cause of morbidity in old patients. Conservative treatment is usually the first line of treatment due to concerns about the risk of surgery. In our study we are trying to assess the outcome of laparoscopic cholecystectomy in patients over 80 years old. Method: Retrospective cohort study done in a large district general hospital where good number of laparoscopic cholecystectomy is done every year. Main outcome is Mortality, return to theatre and post op ITU admission. Data collected from patients records. Results: 74 patients in total were operated on. 14 operations were done as emergency (during the same inpatient admission). Indication for surgery varied between cholecystitis, pancreatitis and biliary colic. But the main indication in the emergency group was acute cholecystitis. 55 % of the patients had significant medical background with ASA 3. 30 days mortality was 0 in both emergency and elective groups. 2 patients required ITU admission post op, mainly for premorbid status, and both were in the emergency group. There was only one return to theatre in the emergency group for washout. 90% of the elective group patients were done as day case with no post op complications. Conclusions: Laparoscopic cholecystectomy is safe operation to be done in the elderly population. ITU admission is mainly because of the patient's co-morbidities so patients should be selected carefully and have proper pre op assessment.